Association of One-Carbon Metabolism-Related Vitamins (Folate, B6, B12), Homocysteine and Methionine With the Risk of Lung Cancer: Systematic Review and Meta-Analysis - Yang, Jia; Li, Hongjia; Deng, Haibin; Wang, Zhongqi (Frontiers in Oncology, 2018)
BACKGROUND: Studies on serum one-carbon metabolism factors (folate, B6, B12, homocysteine and methionine) with lung cancer (LC) risk have produced inconsistent results. We aimed to systematically evaluate the association between them. METHODS: This study was reported in accordance with the PRISMA Statement and was registered with PROSPERO (no. CRD42018086654). Relevant studies were searched in PubMed, Embase, MEDLINE, and CNKI up to February 2018. Random-effects models were used to estimate the pooled standardized mean differences (SMD) or odds ratios (OR), as well as their 95% confidence interval (CI). Sensitivity and subgroup analysis were performed to identify the source of heterogeneity. Publication bias was also assessed. RESULTS: A total of 14 articles (8097 patients) were included. The concentration of serum folate and vitamin B6 of LC patients were lower than the controls [SMD -0.53, 95% CI (-0.70, -0.35), p = 0.001 and SMD -0.28, 95%CI (-0.53, -0.02), p = 0.001, respectively]. While the concentration of homocysteine of the cases was higher than the controls [SMD 0.41, 95% CI (0.24, 0.59), p = 0.001]. However, there were no significant differences between LC patients and the controls in terms of vitamin B12 and methionine [SMD -0.09, 95% CI (-0.27, 0.09), p = 0.202 and SMD -0.13, 95% CI (-0.36, 0.10), p = 0.001]. Subgroup analysis showed that these results were more significant in Europe, Asia, former and current smokers, and the male population (p value < 0.05). CONCLUSIONS: Serum folate and vitamin B6 might be protective factors against lung carcinogenesis and homocysteine could contribute to LC risk.